Altered expression pattern of polycystin-2 in acute and chronic renal tubular diseases - Obermüller, Nicholas; Cai, Yiqiang; Kränzlin, Bettina; Thomson, R. Brent; Gretz, Norbert; Kriz, Wilhelm; Somlo, Stefan; Witzgall, Ralph (Journal of the American Society of Nephrology, 2002)
ABSTRACT. Polycystin-2 represents one of so far two proteins found to be mutated in patients with autosomal-dominant polycystic kidney disease. Evidence obtained from experiments carried out in cell lines and with native kidney tissue strongly suggests that polycystin-2 is located in the endoplasmic reticulum. In the kidney, polycystin-2 is highly expressed in cells of the distal and connecting tubules, where it is located in the basal compartment. It is not known whether the expression of polycystin-2 in the kidney changes or whether it can be manipulated under certain instances. Therefore, the distribution of polycystin-2 under conditions leading to acute and chronic renal failure was analyzed. During ischemic acute renal failure, which affects primarily the S3 segment of the proximal tubule, a pronounced upregulation of polycystin-2 and a predominantly combined homogeneous and punctate cytoplasmic distribution in damaged cells was observed. After thallium-induced acute injury to thick ascending limb cells, polycystin-2 staining assumed a chicken wire-like pattern in damaged cells. In the (cy/+) rat, a model for autosomal-dominant polycystic kidney disease in which cysts originate predominantly from the proximal tubule, polycystin-2 immunoreactivity was lost in some distal tubules. In kidneys from (pcy/pcy) mice, a model for autosomal-recessive polycystic kidney disease in which cyst formation primarily affects distal tubules and collecting ducts, a minor portion of cyst-lining cells cease to express polycystin-2, whereas in the remaining cells, polycystin-2 is retained in their basal compartment. Data show that the expression and cellular distribution of polycystin-2 in different kinds of renal injuries depends on the type of damage and on the nephron-specific response to the injury. After ischemia, polycystin-2 may be upregulated by the injured cells to protect themselves. It is unlikely that polycystin-2 plays a role in cyst formation in the (cy/+) rat and in the (pcy/pcy) mouse.